The Development of Learning Media “English Digital Book” for Tenth Grade Students - Ma’arif, Iin Baroroh; Hidayat, Rohmat; Farida, Siti Nur (STKIP PGRI Ponorogo Press, 2021)
This research aims at developing a learning media which called English Digital Book as English learning media for Tenth grade students of Senior High School. This English Digital Book consists of some materials and exercises which is appropriate and feasible to be studied for students. All materials in this media are based on senior high school syllabus of K13 curriculum. The research method used in this research is Research and Development. This development used ADDIE model which have several steps, those are; 1) analysis, 2) design, 3) development, 4) Implementation, and 5) evaluation. The result of this research shows that from the media validation result got 92 score it was in “very good” category, and the material validation got 95 score it was in “very good” category. The students’ responses of try out result 87 was in “very good category”. By having those result, this English Digital Book is feasible to be used as a learning media for Tenth grade students. Furthermore this research can be used as reference to other researcher in developing English learning media in different level of students.